Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Etos Kerja Tenaga Kependidikan di SMA N 2 Lhoknga Aceh Besar - Sri Rahmi (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
The managerial expertise possessed by school principal, such as the ability to lead, to actuate, to plan and to interact with his/her subordinates is a major factor in achieving the success of the planned programs. School principals should be able to develop a high level of cooperation and work ethic among their subordinates. This article aims to analyse the types of school principal’s managerial expertise and the work ethihc of the teaching staff at State Senior High School 2 Lhoknga, Aceh Besar. The qualitative data was collected through interviews, observation, and documentation. The result shows that the managerial expertises of the principal of State Senior High School 2 Lhoknga includes skills as educator, manager, administrator, supervisor, leader and motivator. The implementation of the expertise went well in accordance with the existing duties, from the planning to the evaluation process. However, the work ethic of the teaching staff has not been running optimally due to two factors, i.e., (1) internal factor which relates to cultural diversity and various; educational-economy-social background; and (2)External factor which relates to wages, work climate, inculcation of attitudes, and time owned by the educational staff.